2022
DOI: 10.1177/07435584221118380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Youths’ Cannabis Health Literacy Post Legalization: A Qualitative Study

Abstract: Legalization of non-medical cannabis in Canada was intended to protect youth health and safety by limiting access and raising awareness of safety and risks. The purpose of this qualitative research was to explore youths’ perceptions of their cannabis health literacy and future educational needs. A convenience sample of youth aged 13 to 18 residing in Newfoundland and Labrador, Canada who may or may not have consumed cannabis were included. A qualitative study using virtual focus groups with semi-structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…program [ 19 , 34 ]. The concept of abstinence as the desired outcome of substance use education persists despite reports that students consider this approach ineffective [ 12 , 13 , 17 ]. These findings highlight the need to further inform educators of the benefits of offering youth evidence-based, harm reduction substance use education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…program [ 19 , 34 ]. The concept of abstinence as the desired outcome of substance use education persists despite reports that students consider this approach ineffective [ 12 , 13 , 17 ]. These findings highlight the need to further inform educators of the benefits of offering youth evidence-based, harm reduction substance use education.…”
Section: Discussionmentioning
confidence: 99%
“…), which is largely unsuccessful at reducing substance use [ 15 , 16 ] and has been described as ineffective by youth [ 12 ]. A harm reduction approach to substance use education is more realistic as it provides strategies to minimize related harms without requiring abstinence as the end goal [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cannabis Health Evaluation and Research Partnership (CHERP) team in Newfoundland and Labrador, Canada, identified a gap in cannabis education for young people within the provincial school system and a desire for interactive, evidence-informed, harm reduction education ( Bishop et al, 2022 ). A scoping review is necessary to identify materials and programming to help inform the future development and inclusion of cannabis content in polysubstance drug education programmes and materials for youth ( Arksey and O’Malley, 2005 ).…”
Section: Introductionmentioning
confidence: 99%